Targeting the inflammasome in Parkinson’s disease - Su, Qi; Ng, Wei Lun; Goh, Suh Yee; Gulam, Muhammad Yaaseen; Wang, Lin-Fa; Tan, Eng-King; Ahn, Matae; Chao, Yin-Xia (Frontiers in Aging Neuroscience, 2022)
Parkinson’s disease (PD) is one of the most common neurodegenerative diseases in which neuroinflammation plays pivotal roles. An important mechanism of neuroinflammation is the NLRP3 inflammasome activation that has been implicated in PD pathogenesis. In this perspective, we will discuss the relationship of some key PD-associated proteins including α-synuclein and Parkin and their contribution to inflammasome activation. We will also review promising inhibitors of NLRP3 inflammasome pathway that have potential as novel PD therapeutics. Finally, we will provide a summary of current and potential in vitro and in vivo models that are available for therapeutic discovery and development.